Analysis of Pillar Foundations and Abutments in The Batu Rasang-Mambulu Village Bridge Project Tambelengan District Sampang Regency - Fairus Zabadi Fairus (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
Today, land transportation is growing and advancing rapidly. As a developing country, of course, Indonesia will always follow technological developments in the field of land transportation, for example implementing policies in improving land transportation facilities, as well as increasing new transportation. Given the importance of land transportation which plays a role in crossing routes from one village to another, a bridge was built. However, the construction of a bridge must be considered carefully, so that the bridge can provide benefits as expected, without compromising the safety element of road users and the bridge itself. This is because bridges play an important role in people's lives. The results of the research on the Batu Rasang-Mambulu village bridge project, Tambelengan District, Sampang Regency, from the analysis of the calculation of the pillar and abutment foundation calculations obtained a total Q > W/M of 1042.31 > 7.14. For the P value of the pile < P permission of 27.54 < 28.43, it was obtained from the sondir test results based on the characteristics of the soil in determining the bearing capacity of the soil.